Evaluasi Penerapan Standar Akuntansi Keuangan Koperasi pada Koperasi Pegawai Republik Indonesia "Tehnologia" SMKN-1 Palangka Raya: Evaluation of The Application of Special Standars of Cooperative Accounting on Cooperative Employee Republic on Indonesia “Tehnologia” SMKN-1 Palangka Raya - Suyati, Endang Sri; Nurbudiyani, Iin; Endriani, Santi (Anterior Jurnal, 2017)
This study aims to find out how the application of special standards of cooperative accounting on Cooperative Employee Republic of Indonesia "Tehnologia" SMKN-1 Palangkaraya. The location for this research took place at the Cooperative Employee of the Republic of Indonesia "Tehnologia" SMKN-1 Palangkaraya, on Tambun Bungai Street and this study was conducted in November 2017. Data collection techniques used in this study are Documentation, namely data collection techniques by collecting some records, management reports, and attachments obtained from the object of research. The method used is descriptive qualitative, that is research with the intention to collect information about the status of existing symptoms, ie symptoms according to what is in the research undertaken. This type or method of study does not use statistical formulas, but by elaborating and giving a logical argument to produce the right conclusions. The conclusions of this research are: 1) Preparation of Financial Statement by Administration Section under Manager's coordination has been done well, 2) The result of preparation of Financial Statement require or needed some more maximal adjustment to PSAK No. 27 (1998 revised edition) about cooperatives. (3) The Member Economic Promotion Report, which is one form of the Cooperative Financial Statement, has not been made by the administration and finance department, and the notes to the financial statements have not provided sufficient information in accordance with PSAK No. 27 about cooperatives.